PENERAPAN MODEL COOPERATIVE LEARNING BERBANTUAN MEDIA SMART LADDER UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENGUKURAN BERAT SISWA KELAS II - Tantri Pranuwita; Fuadiah, Nyiayu Fahriza; Puspa Sari, Eka Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study was the low level of students' conceptual understanding of weight measurement and the limited use of learning models and instructional media that facilitate students in understanding mathematical concepts concretely. This study aimed to determine the improvement in second-grade students' understanding of weight measurement concepts after the implementation of the Cooperative Learning model assisted by Smart Ladder media. This research employed a quantitative approach using an experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 30 second-grade students at SD Negeri 3 Muara Batun. Data were collected through concept understanding tests administered before (pretest) and after (posttest) the treatment. The data were analyzed using descriptive statistics, the normality test, the Paired Sample t-Test, and the N-Gain test. The results showed that the mean pretest score was 56.00, while the mean posttest score increased to 74.33. The Paired Sample t-Test indicated a significance value of 0.000 < 0.05, meaning that Ha was accepted and H₀ was rejected, indicating a significant improvement in students' conceptual understanding after the implementation of the Cooperative Learning model assisted by Smart Ladder media. Furthermore, the average N-Gain score was 0.48 (48.07%), which falls into the moderate category. Therefore, it can be concluded that the implementation of the Cooperative Learning model assisted by Smart Ladder media effectively improved second-grade students' understanding of weight measurement concepts at SD Negeri 3 Muara Batun.